Identification of endoparasites in cow feces in the working area of the Maros Veterinary Center - Kahby, Icha Ayunita; Amrullah, Syarif Hidayat; Dirhamzah,; Wirawan, Hadi Purnama (Teknosains: Media Informasi Sains dan Teknologi, 2024)
Cows are one of the livestock animals that are widely used by humans to fulfill their needs such as meat and milk. However, unclean farming conditions can be a factor in reducing livestock productivity due to parasitic infections. This study aims to determine the type of endoparasite, the symptoms caused, how to identify them, and the kinship between types of endoparasites found in the faeces of cows observed. This study used the buoyancy method (flotation test) and the sedimentation method. The results obtained from 21 cow faecal samples showed there were seven positive samples for each technique with five different species, namely Strongyloides sp., Oesophagostomum sp., Cooperia sp., Paramphistomum sp., and Eimeria sp. Each species will cause almost the same symptoms, such as decreased appetite, weight loss, late growth, metabolic disorders, diarrhea, and several other clinical symptoms that can result in decreased livestock productivity. The key to the determination is used in determining the phylum and class of the species obtained based on their characteristics; the results obtained are species Strongyloides sp., Oesophagostomum sp., Cooperia sp. are in the same phylum Nemathelminthes and class Nematoda, species Paramphistomum sp. is in the phylum Platyhelminthes of the class Trematoda, and the species Eimeria sp. is in the phylum Protozoa of the class Sporozoa. Phylogeny trees are used to see the level of kinship of a species, as in the results obtained that Strongyloides sp., Oesophagostomum sp., and Cooperia sp. is one monophyletic branch because it is in the phylum Nemathelminthes and polyphyletic with Paramphistomum sp. and Eimeria sp. due to the species Paramphistomum sp. is in the phylum Platyhelminthes as well as the species Eimeria sp. is in the phylum Protozoa.